The Curricular Importance of Citizenship Education in Schools in the European Union: Integration of Citizenship Education in the Spanish and German educational curricula - Calatayud Requena, Laura; Guardeño Juan, Mireia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Society is currently facing major challenges to which it must respond. In 2015, the United Nations approved the 2030 Agenda together with the Sustainable Development Goals with the aim of creating a citizenship capable of responding to the needs and challenges of society. Since 1992, Europa felt the need to create a supranational citizenship. The European Unión. Education for Citizenship is perfect for this function and its implementation in the educational systems of the countries is very diverse, resulting in different citizens.